2013
DOI: 10.4236/jfcmv.2013.13013
|View full text |Cite
|
Sign up to set email alerts
|

High Speed Observation of Periodic Cavity Behavior in a Convergent-Divergent Nozzle for Cavitating Water Jet

Abstract: Cloud cavitation shows an unsteady periodic tendency under a certain flow condition. In a cavitating water jet flow with cavitation clouds, the cavities or the clouds produce high impact at their collapse. In order to make clear a mechanism of the periodic cavity behavior, we experimentally examine the behavior in a transparent cylindrical convergent-divergent nozzle using a high-speed video camera. An effect of upstream pressure fluctuation due to a plunger pump is investigated from a viewpoint of unsteady be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 9 publications
(11 reference statements)
3
27
0
Order By: Relevance
“…These images show the unsteady behavior of the cavitating jet, such as the growth of the cavitation cloud downstream of the nozzle followed by shrinking motion due to the reentrant behavior and the shedding. Such periodic behavior of the cavitating jet has been observed by Sato et al [5] in a convergent-divergent nozzle due to the self-resonance behavior in the nozzle. It should be mentioned that a periodic frequency was found to be 1700 Hz in the present experiment, which is obtained from the FFT analysis of the shadowgraph images.…”
Section: Snapshot Pod Analysissupporting
confidence: 55%
“…These images show the unsteady behavior of the cavitating jet, such as the growth of the cavitation cloud downstream of the nozzle followed by shrinking motion due to the reentrant behavior and the shedding. Such periodic behavior of the cavitating jet has been observed by Sato et al [5] in a convergent-divergent nozzle due to the self-resonance behavior in the nozzle. It should be mentioned that a periodic frequency was found to be 1700 Hz in the present experiment, which is obtained from the FFT analysis of the shadowgraph images.…”
Section: Snapshot Pod Analysissupporting
confidence: 55%
“…Hence, the region of interest must be optical accessible. Visualization can thereby be obtained by incident light imaging (de Giorgi et al, 2013), by opposing light imaging (shadow-graphic) (Sato et al, 2013) or by laser light induced luminescence combined with lPIV imaging . In the present work shadow-graphic imaging is used.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…It is also found that there are different fine waves with a higher frequency. According to the previous results by Sato et al [16], it should be noted that there are two kinds of pressure waveforms in the present cavitating nozzle flow and the upstream pressure fluctuating at the lower frequency component is not related to the periodic cavity behavior with higher frequency component, which is typically found in periodical cloud cavitation and peculiar to it.…”
Section: Introductionmentioning
confidence: 99%